STRATEGIC IMPERATIVES OF THE FORMATION OF MILITARY SECURITY IN THE GLOBAL WORLD - Kaspars Kikste (Economics & Education, 2021)
The military security is considered as an important part of national country’s security. Military security is understood as the state of the country's security and its ability to neutralize external threats or internal tensions. Identification of threats and forecasting of conflicts is a key priority of military security and military policy. One of the important components of economic activity can be defined as the military sector as an object of economic management. Ensuring security is one of the key national security issues. In general, military security is understood as the state of a country in which there are opportunities to neutralize or stop destructive attempts to harm or threaten an individual, society, country, the world community, and destabilize peaceful coexistence. In general, the importance of the security system is undeniable for minimizing risks. The article considers the theoretical aspects of security system formation, levels of its implementation and key principles (the key principles of international security are renunciation of dictatorship, violence, equality of rights and interests, reduction of military forces or weapons). In general, the need for military-political cooperation and key aspects of security in a globalized world have been identified. It is determined that the peculiarity of the current stage of formation of the security system is its significant asymmetry on a global scale, the significant prevalence of leading countries by certain criteria over other countries or even associations. In general, in the structure of the military economy, this takes the place of preventing threats, neutralizing them and minimizing negative consequences.